Democratization Articles Dataset: an introduction. Issue 1 (2nd January 2019) - Pelke, Lars; Friesen, Paul
ABSTRACT: This research note introduces the new Democratization Articles Dataset, a survey of peer-reviewed articles on democratization published over the past 25 years from five of the leading comparative politics journals. The data highlight significant gender and location authorship imbalances, while also noting a steady increase in the proportion of female authors as well as team collaboration over the past 25 years. Democratization studies also appear to be largely event driven, with more attention paid to the Post-Soviet countries and democratic transitions in the 1990s, and increased attention to MENA countries and the study of authoritarianism since 2000. The field is also evolving methodologically, with a greater proportion of articles investigating a causal claim, relying on statistical and experimental techniques, and detailing sample selection criteria. Yet, single and comparative cases studies still compose the overwhelming majority of published research articles.